Manipulation of TiH2 Decomposition Kinetics for Two Steps Foaming Method1. Issue 8 (21st February 2014) - He, Si‐Yuan; Jiang, Zong‐Ren; Dai, Ge; Zhang, Yi; Gong, Xiao‐Lu
<x xml:space="preserve">Abstract</x> Two Steps Foaming method is a promising alternative to prepare net‐shaped aluminum foam and aluminum foam core sandwich. In this route, the preoxidized foaming agents are dispersed in aluminum melt and the mixtures are quenched to obtain a foamable precursor. The process parameters are optimized and verified experimentally. It shows that the 500 °C pre‐heated TiH2 dispersed in aluminum melt at a lower dispersion temperature (670 °C) and foamed at a higher temperature (760 °C) is an optimal combination for the Two Steps Foaming method. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>